(3ZGjI GdEJbGf aj JOHjQ HOf GdEfSGfs - (3UGdM Hf fUQ Hf Sdhe GdMdHj,J (B1081 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3adeG cGf Yde GdWH HMQkG dG jOQc dg bQGQ , hJjgG hGSYkG dG jTb dg ZHGQ s
(3BNQgG (B:s
(3MJi jDef ef GdNha hEPG cGf CcKQ ef Pdc UhGHkG s
(3eUOQg HagQS JaUjdis
(3eY PcQ GdUaMI GdJi COQL HgG cd aUds
(3jTJed Ydi (B447(3aUdkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B666 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B132 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs